Determinant of Hypertension among Adults in West Java, Indonesia: Analysis of National Basic Health Research Data 2018 - Karlen, Jannatin; Berbudi, Afiat; Wahyudi, Kurnia (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Hypertension is a serious health problem worldwide. Many studies on the determinants of hypertension have been done, however studies in West Java are still very minimal. This study aimed to determine the risk factors for hypertension among adults in West Java, Indonesia.Methods: This study used a cross-sectional method with a quantitative approach using secondary data from the National Basic Health Research 2018. The final number of individuals sampled was 46,186 people. Data analysis was performed using simple logistic regression and multiple logistic regression methods.Results: The mean age of the sample was 42.97 years (SD=15.37), and females were the predominant (52.95%). The majority of samples consumed sweet beverages (31.06%) and salty foods more than once a day (29.22%), did not smoke (59.17%), had a normal body mass index (BMI) (53.78 %), and had experienced gum disease and dental problems in the last year (56.75 %). Physical activity in metabolic equivalent task (MET) minute was 5,917.79. There was a significant positive association between age and hypertension, with an odds ratio (OR) of 1.06 and a 95% confidence interval (CI) of 1.05–1.06. Furthermore, the analysis found a significant negative correlation between physical activity and hypertension, with an OR of 0.999 and a 95% CI of 0.9999874–0.9999962.Conclusions: Hypertension is significantly associated with age, whereas physical exercise is negatively associated. Priority should be given to elderly individuals and people with a high BMI for interventions such as routine blood pressure monitoring and education.